Pengaruh Pengendalian Pengeluaran dan Gaya Hidup Terhadap Stabilitas Keuangan Mahasiswa FEB - Magali Ilana Meta; Inaya Aidella; Nabila Oktaviansyah; Amanda Salsabila; Saqilla Nur Alaida (Jurnal Manajemen, Akuntansi, Ekonomi, 2026)
This study aims to analyze the effect of expenditure control and lifestyle on the financial stability of students at the Faculty of Economics and Business (FEB). A quantitative associative approach was employed with a sample of 100 students from semesters 4 and 5, selected through purposive sampling. Data were collected via a Likert scale questionnaire (1-5) and analyzed using multiple Linear Regression, T-Test, F-Test, and Coefficient of Determination Test with SPSS application. The results indicate that expenditure control has a positive and significant effetc on financial stability (T-count 5,688 > T-table 1,985; sig. 0,000 < 0,05), while lifestyle has a positive but insignificant effect (T-count 1,183 < T-table 1,985; sig. 0,240 > 0,05). Simultaneously, both variables signifiacntly influence financial stability (F-count 17,361 > F-table 3,09; sig. 0,000 < 0,05), contributing 24,8% to the variance. It is concluded that the ability to control expenditures is a key factor in maintaining financial stability, whereas lifestyle is not a primary determinant as long as students are able to manage their spending effectively.